Analisis Kemampuan Komunikasi Interpersonal Melalui Pertukaran Mahasiswa - Shabrina, Sausan Nur (Jurnal Inovasi Global, 2025)
This study aims to analyze the development of students' interpersonal communication skills through the Merdeka Belajar Kampus Merdeka (MBKM) student exchange program at the University of Mataram in 2022. Using a qualitative case study approach, the research explores students’ experiences during cross-cultural interactions in the Nusantara Module. The findings reveal that intensive interaction in a multicultural environment encouraged students to build empathetic, adaptive, and inclusive communication strategies. Activities such as cultural discussions, local culinary exploration, and participation in traditional events significantly strengthened students' abilities to establish harmonious social relationships. These findings are reinforced by the researcher’s direct experience as a program participant, indicating that involvement in MBKM promotes positive self-concept, confidence, and cross-cultural communication competence. Although students faced challenges such as dialect differences and nonverbal communication styles, they overcame them through accommodative and collaborative approaches. The program proved to provide not only academic benefits but also social and emotional growth, making it a transformative learning space for developing interpersonal skills in a global era.